Fulfilling Children's Participation Rights in Indonesia Through the National Children's Forum Policy - Hastira, Muhammad Fajhriyadi; Maksum, Ali; Hastira, Muh Fichriyadi (Universitas Sultan Ageng Tirtayasa, 2025)
This study describes Indonesia's strategy to ensure children's participation through the National Children's Forum policy. Based on the significant increase in the fulfillment of children's participation rights in Indonesia in the 2018-2022 timeframe and seeing the position of the National Children's Forum (FAN) as a forum and meeting place that discusses children that are attended directly by the only children at the national level who directly or indirectly have the power to be able to provide input on policies regarding the fulfillment of children's rights and protection at the national level to the Indonesian government. The research method used in this study is descriptive qualitative research, which uses interview methods and a literature review to describe the behavior of events in detail based on facts. These are then analyzed to reach analytical conclusions to the research questions. The findings of this research show that Indonesia's policies in guaranteeing children's participation rights include the establishment of the National Children's Forum by the Ministry of Women's Empowerment and Child Protection. These efforts include regulations, indicators of Child-Friendly Districts/Cities, and the establishment of Children's Forums down to the village level. The Ministry of Women's Empowerment and Child Protection also involves families, schools, and communities through special programs. Indonesia is active in regional and international forums, such as the ACF, which influence the formation of policies related to children's rights. These strategies demonstrate Indonesia's commitment to realizing child participation at various levels.